Assessment and Strategies to Reduce Light Pollution Using Geographic Information Systems. (2015) - Elsahragty, Mohamed; Kim, Jin-Lee
Abstract: Light pollution is a negative lighting condition because it prevents views of the night sky from the general population and astronomers. As a solution to light pollution, proper lighting system design is vital. The location, mounting height, and aim of exterior luminaries need to be taken into consideration for efficient use of lighting energy. In line with the effort, this paper presents the assessment results on light pollution at the port area, which is one of the brightest spots on Earth. In doing so, a GIS model is created to determine the level of light pollution at the study areas. The lighting power densities of ASHRAE 90.1-2007 are applied in order to find a way to reduce the level of light pollution. The effect of light pollution generated from the Long Beach Port area is examined by comparing against the sky glow generated from the Port of Long Beach area and other areas throughout the coast of Southern California, as well as comparing how deep the sky glow penetrates the ocean. The results are validated by comparing against the lighting specification used in the study areas. The lighting strategies proposed include the decreased height of light poles and increased spacing between light poles. This study will serve as a platform in which future researchers may continue and expand on the designs of heights and spaces of lighting poles in order to make severe light pollution areas better sustainable places.